Farmer variety exchange along Amazonian rivers influences the genetic structure of manioc maintained in a regional Brazilian GeneBank - Sousa, S. B.; Silva, G. F.; Dias, Miguel Costa; Clement, Charles Roland; Sousa, Nelcimar Reis (Genetics and Molecular Research, 2017)
Knowledge of agro-morphological and genetic variability of germplasm diversity is a prerequisite for its use in breeding. The aim of this study was to characterize the genetic diversity of the manioc (Manihot esculenta) Active Germplasm Bank (AGB) at Embrapa Amazônia Ocidental using microsatellite markers. We evaluated 470 accessions collected along five of the main rivers of the Amazon basin: Solimões, Purus, Madeira, Negro, and Amazon. The ten SSR loci used showed high levels of genetic diversity, the polymorphism information content ranged from 0.35 to 0.84, and the mean number of alleles per locus was 11.3. Accessions from the Madeira River had a higher Shannon index (1.52), as well as the largest number of private alleles (19). Bayesian inference of genetic structure implemented in the Structure software suggested the existence of two groups of accessions without clear association with river basins. The accumulated variation in the first two axes of the principal coordinate analysis revealed low genetic divergence between these groups, while AMOVA identified most of the molecular variance within the groups. Farmer exchange of varieties along and among rivers probably explains the lack of structure. Although the manioc AGB of Embrapa Amazônia Ocidental contains abundant genetic diversity, no differentiation was found between the groups studied. © 2017 The Authors.
Keywords: Agricultural Worker; Allele; Bitter Taste; Cassava; Conservational Seed Bank; Controlled Study; Gene Structures; Polymorphism, Genetic; Genetic Variability; Human; Human Experiment; Madeira; Microsatellite Marker; Nonhuman; Principal Coordinate Analysis; River Basin; Software